Assessment of tumour response after stereotactic ablative radiation therapy for lung cancer: A prospective quantitative hybrid 18F‐fluorodeoxyglucose‐positron emission tomography and CT perfusion study. Issue 1 (3rd October 2018) - Yang, Dae‐Myoung; Palma, David; Louie, Alexander; Malthaner, Richard; Fortin, Dalilah; Rodrigues, George; Yaremko, Brian; Laba, Joanna; Gaede, Stewart; Warner, Andrew; Inculet, Richard; Lee, Ting‐Yim
Abstract: Introduction: Stereotactic ablative radiotherapy (SABR) is a guideline‐recommended treatment for inoperable stage I non‐small cell lung cancer (NSCLC), but imaging assessment of response after SABR is difficult. The goal of this study was to evaluate imaging‐based biomarkers of tumour response using dynamic 18 F‐FDG‐PET and CT perfusion (CTP). Methods: Thirty‐one patients with early‐stage NSCLC participated in this prospective correlative study. Each underwent dynamic 18 F‐FDG‐PET/CTP studies on a PET/CT scanner pre‐ and 8 weeks post‐SABR. The dynamic 18 F‐FDG‐PET measured the tumour SUVmax, SUVmean and the following parameters: K1, k 2, k 3, k 4 and K i, all using the Johnson–Wilson–Lee kinetic model. CTP quantitatively mapped BF, BV, MTT and PS in tumours and measured largest tumour diameter. Since free‐breathing was allowed during CTP scanning, non‐rigid image registration of CT images was applied to minimize misregistration before generating the CTP functional maps. Differences between pre‐ and post‐SABR imaging‐based parameters were compared. Results: Tumour size changed only slightly after SABR (median 26 mm pre‐SABR vs. 23 mm post‐SABR; P  = 0.01). However, dynamic 18 F‐FDG‐PET and CTP study showed substantial and significant changes in SUVmax, SUVmean, k 3, k 4 and K i . Significant decreases were evident in SUVmax (median 6.1 vs. 2.6; P  < 0.001), SUVmean (median 2.5 vs. 1.5; P  < 0.001), k 3 (relative decrease of 52%; P  = 0.002), K i (relative decrease of 27%; P  = 0.03), whereas there was an increase in k 4 (+367%; P  < 0.001). Conclusions: Hybrid 18 F‐FDG‐PET/CTP allowed the response of NSCLC to SABR to be assessed regarding metabolic and functional parameters. Future studies are needed, with correlation with long‐term outcomes, to evaluate these findings as potential imaging biomarkers of response.